2017
DOI: 10.1245/s10434-017-5781-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Outpatient Pain Management After Thyroid and Parathyroid Surgery: A Two-Institution Experience

Abstract: Background Thyroidectomy and parathyroidectomy are the most commonly performed endocrine operations, and increasingly are completed on a same-day basis. Little data exists regarding the outpatient post-operative pain requirement of these patients. We aimed to describe the outpatient narcotic medication needs for patients undergoing thyroid and parathyroid surgery, and to identify predictors of higher requirement. Method We examined patients undergoing thyroid and parathyroid surgery at two large academic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
68
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 20 publications
10
68
3
Order By: Relevance
“…Our study results, in line to what is reported in the literature, show that higher reported maximum and last pain scores before discharge are associated with higher postoperative opioid need. 13 Interestingly, our study did not find an association between opioid consumption and other factors that are known to predict opioid need including patients' age, sex, and history of depression or anxiety. 12,14,15 Depression or anxiety rates were higher in top opioid users compared to standard users, but the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Our study results, in line to what is reported in the literature, show that higher reported maximum and last pain scores before discharge are associated with higher postoperative opioid need. 13 Interestingly, our study did not find an association between opioid consumption and other factors that are known to predict opioid need including patients' age, sex, and history of depression or anxiety. 12,14,15 Depression or anxiety rates were higher in top opioid users compared to standard users, but the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 75%
“…Another study assessed opioid requirement after thyroidectomy and parathyroidectomy and found no difference between unilateral and bilateral neck exploration but patients undergoing thyroidectomy required more opioid compared to parathyroidectomy. 13 However, 93% of all patients included in that study required less than 20 MME which is equivalent to 2.6 tablets of 5 mg oxycodone. 13 Thus, we recommend prescribing nonopioid analgesic for patients undergoing these procedures as their opioid needs do not justify prescriptions and our results suggest that over 95% of them did not dispose the leftover opioids.…”
Section: Discussionmentioning
confidence: 98%
“…Postoperative pain after thyroid surgery is normally moderate and limited to the first few days, usually necessitating pain medication with non‐opioid analgesics. Some patients need rescue medication with opioids in this early period, which potentially delays hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond divergent prescribing patterns, it is becoming quite apparent that the vast majority of post‐thyroidectomy and parathyroidectomy patients are likely receiving total amounts of opioids far in excess of their pain control needs. Lou et al prospectively analyzed their institutional prescribing patterns and found that despite being prescribed up to 120 MME, the pain requirements of 93% of patients were adequately addressed with <20 MME . Another single institution study revealed that post‐thyroidectomy patients were routinely prescribed enough opioids to satisfy regular use for a 14‐day duration despite a mean discharge pain score of 3 on a standard 0‐10 scale .…”
Section: Discussionmentioning
confidence: 99%
“…Next, we recognize that the use of ordinal ranges of prescribed tablets may have resulted in decreased precision in fully assessing the true amounts of opioids typically prescribed by our surveyed cohort, and this is perhaps the primary limitation of this study. These ranges were selected based on commonly reported amounts of prescribed tablets, and the corresponding survey question was structured to simplify and streamline the survey to encourage a higher overall RR. That being said, this approach did result in a somewhat arbitrary grouping that might overstate the variations and mischaracterize the more subtle nuances in opioid‐prescribing patterns among our cohort.…”
Section: Discussionmentioning
confidence: 99%